If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3 + k Solving 7 = 3 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 7 + -1k = 3 + k + -1k Combine like terms: k + -1k = 0 7 + -1k = 3 + 0 7 + -1k = 3 Add '-7' to each side of the equation. 7 + -7 + -1k = 3 + -7 Combine like terms: 7 + -7 = 0 0 + -1k = 3 + -7 -1k = 3 + -7 Combine like terms: 3 + -7 = -4 -1k = -4 Divide each side by '-1'. k = 4 Simplifying k = 4
| 74-60x=300 | | -2h=-18 | | 6+5x=-4x+57 | | c=35+0.03 | | ln(2x+6)=7 | | 0.7W+164w=27.28 | | ln(2x+6)=6 | | 8x+2=114 | | s/5=-13 | | -3+13=12x-5-11x | | (2x-3)(2x+3)-4x(x+1)=2(x+3)+3 | | 2q-2=23 | | .35=.50 | | 2m-(x+2)=0 | | log4x=5/2 | | (X+2y)(x^3-2x^2y+4xy^2)= | | 3-1/2x=-5 | | 4x=-7y-37 | | 9x-3+2x+20=15+4x+2+7x | | 2x+17-7x-6=8-10x-19+5x | | (5x+3)2y=43 | | 5(3x+3)-5x=95 | | (3x-6)+(5x+9)= | | (7x+2)2= | | (7/9)+(5/6)=x | | 4a+7b=43 | | (4/9)-(1/2)=x | | 5s+20=150 | | x+.8x=25 | | 44=5x-4 | | X+2x=145 | | x+(3x-2)+(4x-4)= |